Modelo de system dynamics para a gestão de resíduos sólidos no município de Araraquara-SP - Pinha, Augusto Cesar Hernandes (Universidade Federal de São Carlos, 2019)
The efficient management of municipal solid waste is one of the objectives of public administration, especially considering the compliance with the legislation in force since 2010, with the enactment of Law 12,305. Therefore, managers should have available all the tools that can assist them in decision making and enable them to carry out projections, preferably in the long term, in order to meet this requirement. One of these tools is modeling and simulation. This work aims to present a System Dynamics model that allows managers to simulate and forecast certain scenarios that influence the generation of solid waste, as well as a model that supports decision making regarding the necessary treatment and resources for such end. The proposed model aims to determine, for a period of 10 years, the population of Araraquara and the amount of generated waste, separating it by type, namely paper, plastics, metals, glass and other residues. The actually recycled quantity and the costs and revenues involved in the process are also determined. With the developed model, six scenarios were proposed, each of which presents a different situation of the city and the Cooperative in charge of the collection and sorting of the recyclable material. The first scenario is where there is no change and the last one is where the city increases its capacity for selective collection and implements composting and the Cooperativa increases the efficiency of its activities. After simulations, it was concluded that scenario five, in which there is an increase in the amount of waste collected by the Selective Collection and an improvement in the process of sorting and separation presents positive results to the city with a viable investment to be executed by the Public Authorities. This work contributed to the literature by expanding the existing models and making a greater detail of the types of wastes collected and commercialized, as well as their quantities and the actual value practiced. In addition, it was possible to make a financial analysis from the simulated scenarios, showing the revenues and expenses existing in the process and their growth over time. It allowed to analyze that only the revenue obtained with the commercialization of the recyclables is not sufficient to supply the expenses of the Cooperative, being necessary the union with the Public Authorities and with other ones in order to increase the bargaining power of negotiation.
System dynamics model for solid waste management in Araraquara-SP
Keywords: Gestão Municipal de Resíduos Sólidos; Coleta seletiva; Modelagem; Tomada de decisão; Cenários; Municipal Solid Waste Management; Selective collection; Modeling; Decision taking; Scenarios; System dynamics; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO